Usability Evaluation of Azkiya Creative Application at Pondok Pesantren Modern Al-Azkiya' Pengalihan Keritang Village Using the System Usability Scale (SUS) Method Al-Azkiya’ Desa Pengalihan Keritang Menggunakan Metode System Usability Scale (Sus) - samsudin, samsudin; syamsiah, andi; Ilyas, Ilyas (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
One of the innovations that emerged in the environment of the modern boarding school al-azkiya'' is the Azkiya Creative application, which is designed to be an application that contains books / bibles, as well as religious materials. To assess whether the application provided has a usability value for users, it is necessary to conduct an evaluation to measure the level of usability. This evaluation aims to identify the advantages, disadvantages, and potential improvements of the existing system. The research to be carried out consists of several stages, namely literature study, data collection, data analysis, and conclusions. In this study using the SUS (System Usability Scale) method to evaluate the azkiya creative application. Researchers distributed SUS questionnaires that respondents had to fill out, then the data was processed so as to produce output, namely usability testing using the System Usability Scale method. regarding the evaluation of the azkiya creative application, the respondents were teachers who had or were using the azkiya creative application. the results of research conducted on 30 respondents, can be obtained the average score through a questionnaire with a score of 80.5. In terms of Acceptability assessing the azkiya creative application at Pondok Pesantren Modern Al-Azkiya' is categorized as acceptable, Grade Scale assesses the application from the aspect of quality level, the evaluation results show that the azkiya creative application is on grade scale B, and Adjective is categorized as excellent in the azkiya creative application.